The Influence of Microwave on Reduced Graphene Oxide (rGO) Crystallinity from Inorganic Waste - Lubis, Lailatul Husna; Husnah, Miftahul (Universitas Islam Negeri Ar-Raniry, 2020)
The synthesis of reduced graphene oxide was carried out using the smoke catcher method and inorganic waste. The inorganic waste smoke obtained became the basic material as a carbon source. After burning the inorganic waste, the smoke collected was in the form of a powder and exposed to microwaves. Based on FTIR characterization, the synthesis was successfully carried out by obtaining 1600 cm-1 as the peak of the aromatic functional group (C = C) or graphene functional group. After the inorganic waste smoke sample was put in the microwave, the rGO sample was obtained which had a higher crystallinity than before heating in the microwave.